Utilizing Augmented Reality Technology to Create an Immersive Learning Experience - Andy Rachman; Muhammad Subhan Iswahyudi; Brian Sebastian Salim; Widiharto Purnomo; Wahyu U. Putra (P3M IAI Nusantara Batang Hari, 2024)
Education is a process of reducing the number of ignorance and poverty in the world. Through education a person can change his life, far more advanced than people who are not educated. In today's advanced and sophisticated era, education is supported by the presence of various technologies. With technology, one can create interactive and creative education. Various kinds of technology emerged and developed. This rapidly developing technology also encourages the birth of a process of change in the world of education. The presence of this technology provides many benefits in the world of education. The purpose of this study is to find out the benefits of augmented reality technology in creating deep learning. The method used in this study is a quantitative research method with a survey design. Data for this study were obtained by filling out a questionnaire via the Google Forms link. The results of this study are that the benefits of augmented reality technology in creating in-depth learning have a significant influence and impact on the learning process. Through Augmented Reality Technology has the opportunity to improve the learning process in high school. Learning that uses AR technology allows students to learn in a more exciting, fun and interactive way. In addition, AR technology can also make students better understand the concept of learning. The limitation of this research is that the researcher only investigated at the school level. The researcher also hopes that future researchers can take this research to a higher level and he also hopes that in the future there will be other researchers who can advance this research.